2015
DOI: 10.1111/1462-2920.12895
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to soil, house dust and decaying plants increases gut microbial diversity and decreases serum immunoglobulin E levels in BALB/c mice

Abstract: To assess the impact of sanitation of a living environment on gut microbiota and development of the immune system, we raised BALB/c mice under three distinct environmental conditions: a specific pathogen-free animal room (SPF), a general animal room (XZ) and a farmhouse (JD). All other variables like diet, age, genetic background, physiological status and original gut microbiota were controlled for in the three groups. Using high-throughput sequencing of the 16S rRNA gene, we found that each mouse group had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 38 publications
1
73
3
1
Order By: Relevance
“…All other variables like diet, age, genetic background, physiological status, and original gut microbiota were controlled. The results show that mice from a sanitary environment had more diverse microbiota and a higher ratio of Bacteroidetes to Firmicutes [17] , which has previously been shown to be good for human health.…”
Section: Research Highlightmentioning
confidence: 75%
See 1 more Smart Citation
“…All other variables like diet, age, genetic background, physiological status, and original gut microbiota were controlled. The results show that mice from a sanitary environment had more diverse microbiota and a higher ratio of Bacteroidetes to Firmicutes [17] , which has previously been shown to be good for human health.…”
Section: Research Highlightmentioning
confidence: 75%
“…To answer the above question, we raised BALB/c mice under three distinct environmental conditions: a specific pathogen free animal room, a general animal room, and a farmhouse [17] . All other variables like diet, age, genetic background, physiological status, and original gut microbiota were controlled.…”
Section: Research Highlightmentioning
confidence: 99%
“…A possible reason for this is the complex farm environment where pollution is more serious. Studies have shown that mice in a farmhouse harbored a significantly more diverse and richer gut microbiota, due to their exposure to unhygienic conditions, compared with mice reared in a specific pathogen-free animal room (Zhou et al 2016). The cultured R. dybowskii is susceptible to disease (Weng et al 2016), and the treatment options are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The high-throughput sequencing of 16S rRNA gene demonstrated that the microbiomes of three groups of mice kept in three different environments, including (i) specific pathogen-free animal rooms, (ii) general animal rooms and (iii) farmhouses were different. The enhanced gut microbial diversity, a sign of a healthy microbiome, mostly occurred in the second and third groups whose serum IgE levels were reduced as well (Zhou et al, 2016). The soil components related to a healthier microbiome remain to be identified, and that the soil Streptomycetes can be very attractive candidates.…”
Section: Mucosal Microbiomes and Streptomycetesmentioning
confidence: 99%
“…Their abundance in animals eating directly from nature is more than humans (Wang et al, 2014;Zhang et al, 2015;Rabelo-Fernandez et al, 2018). For example, Zhang et al investigated the rodent's gut microbiome and found that Streptomycetes constitute around 10% of the phylum Actinobacteria that accounted for 11% of rodent's gut microbiome living in a farmhouse (Zhang et al, 2015;Zhou et al, 2016). Streptomycetes were reported in the lower abundance taxa (< 0.5%) in humans (Li et al, 2014;Raymond et al, 2016) whose lifestyle has been significantly changed during the last century.…”
Section: Mucosal Microbiomes and Streptomycetesmentioning
confidence: 99%